(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the short-term functional outcomes and complications of reverse shoulder arthroplasty in an initial case series with different indications. Methods: A prospective case series study of 12 patients who underwent reverse shoulder arthroplasty from January 2025 to September 2025. Outcomes were assessed using the VAS, ASES scores, and shoulder range of motion at a minimum follow-up of 6 months postoperatively. Results: The mean age was 64.8 ± 9.8 years. Humeral head osteonecrosis and secondary glenohumeral osteoarthritis following rotator cuff tear were the most common indications (58.3%). Other indications included primary glenohumeral osteoarthritis (16.7%), complex proximal humerus fractures in the elderly, massive irreparable rotator cuff tears, and failed open reduction and internal fixation, each accounting for 8.3%. Mean follow-up was 6.0 ± 0.5 months. Functional outcomes: VAS 2 ± 0.8, ASES 68.8 ± 5.2, forward flexion 122.5° ± 18.3°, abduction 111.7° ± 27.9°, external rotation 23.3° ± 6.6°. No serious complications or revision surgeries were recorded. Conclusion: In this initial case series, reverse shoulder arthroplasty showed low postoperative pain, acceptable functional outcomes, and no serious complications at short-term follow-up. Further studies with larger sample sizes and longer follow-up are needed to better evaluate the effectiveness of this procedure.